2021
DOI: 10.1016/j.tecto.2021.228736
|View full text |Cite
|
Sign up to set email alerts
|

Shear deformation of nano- and micro-crystalline olivine at seismic slip rates

Abstract: Shear deformation of nano-and micro-crystalline olivine at seismic slip rates. Tectonophysics,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 120 publications
(146 reference statements)
0
1
0
Order By: Relevance
“…Dislocation microstructures produced in laboratory deformation experiments have been used for comparisons with those produced in nature in order to help determine whether the same rate-controlling creep mechanisms also operate in natural environments [6]. Recently, a growing number of controlled deformation studies have been carried out on olivine using an apparatus known as the deformation DIA (D-DIA) [11][12][13][14][15][16]. There were some studies with the D-DIA that showed the transition from (010)[100] and (001)[100] slip systems (hereafter referred to as a-slip) at low pressures to (010)[001] and (100)[001] slip systems (hereafter referred to as c-slip) at high pressures [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Dislocation microstructures produced in laboratory deformation experiments have been used for comparisons with those produced in nature in order to help determine whether the same rate-controlling creep mechanisms also operate in natural environments [6]. Recently, a growing number of controlled deformation studies have been carried out on olivine using an apparatus known as the deformation DIA (D-DIA) [11][12][13][14][15][16]. There were some studies with the D-DIA that showed the transition from (010)[100] and (001)[100] slip systems (hereafter referred to as a-slip) at low pressures to (010)[001] and (100)[001] slip systems (hereafter referred to as c-slip) at high pressures [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%